1976
DOI: 10.1515/botm.1976.19.5.273
|View full text |Cite
|
Sign up to set email alerts
|

Marine Algae of the Greek West Coast

Abstract: The main purpose of this research was to study the marine flora in the midlittoral and upper mfralittoral zones of the Greek west coast. About 175 species were noticed in the 11 localities selected for study: 33 green algae, 36 brown algae, 101 red algae, 2 blue-green algae and 3 marine phanerogams. The ratio R/P = 2.86 indicates a more boreal than subtropical type of Vegetation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 9 publications
(14 reference statements)
0
16
0
3
Order By: Relevance
“…This rare Mediterranean endemic has been reported from various localities in the Aegean and Ionian Seas (Gerloff & Geissler, 1974;Haritonidis & Tsekos, 1976;Tsekos et al, 1982). Nevertheless, Alongi et al (2002) reported that the only herbarium specimens from Greece (Attica), located at the Riksherbarium in Stockholm and labelled as C. squarrosa, belonged to C. corniculata.…”
Section: Cystoseira Squarrosa De Notarismentioning
confidence: 69%
See 3 more Smart Citations
“…This rare Mediterranean endemic has been reported from various localities in the Aegean and Ionian Seas (Gerloff & Geissler, 1974;Haritonidis & Tsekos, 1976;Tsekos et al, 1982). Nevertheless, Alongi et al (2002) reported that the only herbarium specimens from Greece (Attica), located at the Riksherbarium in Stockholm and labelled as C. squarrosa, belonged to C. corniculata.…”
Section: Cystoseira Squarrosa De Notarismentioning
confidence: 69%
“…Silva = Sorocarpus uvaeformis (Lyngbye) Pringsheim Athanasiadis (1987) excluded the record of Politis (1936, as Sorocarpus uvaeformis Pringsheim) from Attica, since this cold-temperate alga was not known elsewhere in the Mediterranean. Botrytella micromora was previously reported in the Ionian Sea by Haritonidis & Tsekos (1976) and Tsekos & Haritonidis (1977, as Sorocarpus micromorus), but without descriptions or illustrations. Since then, this North Atlantic-Arctic species has been reported from the strait of Dardanelles (Taskin, 2008, Fig.…”
Section: Padina Di-tristromaticamentioning
confidence: 93%
See 2 more Smart Citations
“…The purpose of this study is to assess the benthic communities' state three and a half years after the event, and compare it with that described by Haritonidis and Tsekos (1976).…”
Section: Introductionmentioning
confidence: 99%